(untitled) (Journal of the College of Basic Education, 2022)
In Tom Stoppard’s 1964 short story, "Life, Times: Fragments," the writer-protagonist seeks originality by consciously denying the influence of previous writers. His first person accounts, however, are inevitably derivative, filled with haunting echoes of the very writers he has supposedly killed off by the force of his own self-originary powers. Of this, Stoppard says: "Artistic recycling, dramatic allusion, intertextuality, parody, travesty- are not only inevitable, but necessary. It is only in the interweaving of texts that the new text emerges."(qtd in Kinereth Meyer, p.105)